Prevalence and management of poststroke spasticity in Thai stroke patients: A multicenter study - Dajpratham P. (2014)
Objectives: To study the prevalence, associated factors and management of poststroke spasticity in two muscle groups namely elbow flexor and knee flexor. Material and Method: The Thai stroke rehabilitation registry (TSRR) was conducted among 9 rehabilitation centers. All subjects received the conventional rehabilitation program until they reached their rehabilitation goals or discharge criteria. The Brunnstrom motor recovery stage, Barthel Index, Thai Mental State Examination, Modified Ashworth Scale (MAS), and WHOQOL-BREF-Thai(26 items) questionnaires were used to assess the motor recovery, functional disability, cognition, spasticity and quality of life on admission respectively. The management of spasticity was also recorded. Results: There were 327 patients with a mean age of 62.2 years old participating in the study. The prevalence of poststroke spasticity was 41.6%. Among these the prevalences of spasticity of both elbow and knee flexors was 31.2% and of either elbow or knee flexor were 4.9% and 5.5% respectively. Spasticity with MAS grade 1 was found in the majority. The patients with spasticity had a significantly longer time to rehabilitation admission interval after the stroke (p = 0.049), had the Brunnstrom motor recovery stages of arm (p < 0.001), hand (p = 0.003) and leg (p < 0.001) significantly lower than the no spasticity group. The factor associated with spasticity was Brunnstrom motor recovery stage 2 and 3 of the arm with the odds ratio being 6.1 (95% CI = 2.5-14.9) and 3.5 respectively (95% CI = 1.3-9.2). Management of spasticity was demonstrated in 83 patients (25.4%). Therapeutic exercise, oral antispastic medication and assistive device were the first three managements frequently prescribed respectively. Conclusion: Spasticity was a common complication after stroke. Although the prevalence was quite high, spasticity with MAS grade 1 was found in the majority of cases. The associated factor was the Brunnstrom motor recovery stage of the arm. Therapeutic exercise was the mainstay of the management.